Maternal effects on offspring stress physiology in wild chimpanzees. Issue 1 (12th January 2016) - Murray, Carson M.; Stanton, Margaret A.; Wellens, Kaitlin R.; Santymire, Rachel M.; Heintz, Matthew R.; Lonsdorf, Elizabeth V.
Abstract : Early life experiences are known to influence hypothalamic‐pituitary‐adrenal (HPA) axis development, which can impact health outcomes through the individual's ability to mount appropriate physiological reactions to stressors. In primates, these early experiences are most often mediated through the mother and can include the physiological environment experienced during gestation. Here, we investigate stress physiology of dependent offspring in wild chimpanzees for the first time and examine whether differences in maternal stress physiology are related to differences in offspring stress physiology. Specifically, we explore the relationship between maternal rank and maternal fecal glucocorticoid metabolite (FGM) concentration during pregnancy and early lactation (first 6 months post‐partum) and examine whether differences based on maternal rank are associated with dependent offspring FGM concentrations. We found that low‐ranking females exhibited significantly higher FGM concentrations during pregnancy than during the first 6 months of lactation. Furthermore, during pregnancy, low‐ranking females experienced significantly higher FGM concentrations than high‐ranking females. As for dependent offspring, we found that male offspring of low‐ranking mothers experienced stronger decreases in FGM concentrations as they aged compared to males with high‐ranking mothers or their dependent female counterparts. Together, these results suggest that maternal rank and FGM concentrations experienced during gestation are related to offspring stress physiology and that this relationship is particularly pronounced in males compared to females. Importantly, this study provides the first evidence for maternal effects on the development of offspring HPA function in wild chimpanzees, which likely relates to subsequent health and fitness outcomes. Am. J. Primatol. 80:e22525, 2018. © 2016 Wiley Periodicals, Inc.